A REVIEW OF CLINICAL STUDIES OF ANTICANCER ACTIVITY OF ARTEMISININ DERIVATIVE - D. A. Konovalov; A. A. Khamilonov; O. M. Shevchuk; L. A. Logvinenko (Фармация и фармакология (Пятигорск), 2018)
Artemisinin is a sesquiterpene lactone isolated from the aerial part of sweet wormwood (Artemisia annua L.) in the 1970s. Based on its derivatives, the most effective medicines for the treatment of malaria have been created and are widely used. Over the past two decades, numerous in vitro and in vivo studies have been performed. They have shown the anticancer activity of these drugs in relation to certain cancer cell lines. The aim of the study is the review the scientific information on the clinical cases and the results of clinical trials carried out using drugs based on artemisinin derivatives. Material and methods. The study was conducted with the use of information search (PubMed, ScholarGoogle,) and library databases (Cochrane, eLibrary, Cyberleninca), as well as ResearchGate application for semantic search. Results and discussion. It has been established that the largest number of known clinical cases and completed clinical studies is associated with the study of the anticancer activity of one of the artemisinin derivatives - artesunate. The data obtained by various research groups do not yet allow us to speak of a pronounced activity of the latter. However, the facts of prolonging the life of patients, improving its quality, increasing control over the disease have been established. Conclusion. The published data of clinical cases and clinical studies performed for the period from 2001 to 2016, instill restrained optimism about the prospect of using drugs based on some artemisinin derivatives in oncology.